Fpr2/CXCL1/2 Controls Rapid Neutrophil Infiltration to Inhibit Streptococcus agalactiae Infection - Sun, Zeyu; Huang, Wenhua; Zheng, Yuling; Liu, Peng; Yang, Wenbo; Guo, Zinan; Kong, Decong; Lv, Qingyu; Zhou, Xinyu; Du, Zongmin; Jiang, Hua; Jiang, Yongqiang (Frontiers in Immunology, 2021)
Streptococcus agalactiae, also known as group B streptococcus (GBS), can cause pneumonia, meningitis, and bacteremia, making it a pathogen that can increase the risk of death in newborns and immunodeficient individuals. PMN is the first barrier to a host’s innate immune defense against these infections. Fpr2 is an important chemotactic receptor of PMN, though its activation would cause positive and negative effects. In this study, we found that mice without Fpr2 receptors were highly susceptible to GBS infections. These mice demonstrated decreased chemotaxis to PMN, decreased bactericidal ability of PMN, and high mortality. RNA-seq and Luminex assay indicated that Fpr2 activates key signal molecules downstream and produces chemokine CXCL1/2 to chemotaxis PMN. Like Fpr2-/-, CXCL1/2 or Neutrophil depletion impairs host’s ability to defend against GBS infection. Altogether, these data indicate that Fpr2 contributes to a host’s ability to control GBS infection and that a lack of Fpr2 was associated with selective impairment during the production of chemokines CXCL1 and CXCL2 as well as neutrophil recruitment. We also clarified that Fpr2 was a chemotactic receptor, and can chemotactic PMN directly and control infections by chemotactic PMN by regulating chemokine production.